Sons from afar - Voigt, Cynthia (New York : Atheneum, 1987)
Six years after coming to live with their grandmother, James and Sammy Tillerman go in search of their long-lost father.
Booklist.
Notable/Best Books (A.L.A.).
Publisher's Weekly.
7.0
7.0
7-10.
Keywords: Brothers -- Fiction; Fathers -- Fiction; Brothers -- Fiction; Fathers -- Fiction